A comparison of image and observer based aerial surveys of narwhal. Issue 4 (31st January 2019) - Bröker, Koen C. A.; Hansen, Rikke G.; Leonard, Kathleen E.; Koski, William R.; Heide‐Jørgensen, Mads Peter
Abstract: From 25 to 30 August 2014 a double‐observer line‐transect survey was conducted over Melville Bay, home to one of two summering populations of narwhal ( Monodon monoceros ) off West Greenland. A total of 1, 932 linear kilometers was surveyed along 33 transects. In addition to using observers, the aircraft was equipped with two oblique cameras to capture a comparable data set. Analysts reviewed the images for narwhal sightings, which were then matched to the observer sightings. The objectives of the study were to determine advantages and disadvantages of the detection capabilities of both methodologies, and to conduct a comparative analysis of population abundance estimates. Correcting for the truncated detection distance of the images (500 m), the image analysts recorded more sightings (62) and a lower mean group size (2.2) compared to aerial observers (36 and 3.5, respectively), resulting in comparable numbers of individuals detected by both platforms (135 vs . 126). The abundance estimate based on the image sightings was 2, 536 (CV = 0.51, 95% CI: 1, 003–6, 406), which was not significantly different from the aerial observers estimate of 2, 596 individuals (CV = 0.51; 95% CI: 961–7, 008). This study supports the potential of using UAS for marine mammal abundance studies.